SOD1 targeted to the mitochondrial intermembrane space prevents motor neuropathy in the Sod1 knockout mouse - Fischer, Lindsey R.; Igoudjil, Anissa; Magrané, Jordi; Li, Yingjie; Hansen, Jason M.; Manfredi, Giovanni; Glass, Jonathan D. (Brain (London, England : 1878), 2011)
Motor axon degeneration is a critical but poorly understood event leading to weakness and muscle atrophy in motor neuron diseases. Here, we investigated oxidative stress-mediated axonal degeneration in mice lacking the antioxidant enzyme, Cu,Zn superoxide dismutase (SOD1). We demonstrate a progressive motor axonopathy in these mice and show that Sod1(-/-) primary motor neurons extend short axons in vitro with reduced mitochondrial density. Sod1(-/-) neurons also show oxidation of mitochondrial--but not cytosolic--thioredoxin, suggesting that loss of SOD1 causes preferential oxidative stress in mitochondria, a primary source of superoxide in cells. SOD1 is widely regarded as the cytosolic isoform of superoxide dismutase, but is also found in the mitochondrial intermembrane space. The functional significance of SOD1 in the intermembrane space is unknown. We used a transgenic approach to express SOD1 exclusively in the intermembrane space and found that mitochondrial SOD1 is sufficient to prevent biochemical and morphological defects in the Sod1(-/-) model, and to rescue the motor phenotype of these mice when followed to 12 months of age. These results suggest that SOD1 in the mitochondrial intermembrane space is fundamental for motor axon maintenance, and implicate oxidative damage initiated at mitochondrial sites in the pathogenesis of motor axon degeneration.